Ozonation of corn grits (Zea mays L.) in high concentrations promotes change in color and aroma of the product (Research, Society and Development, 2022)
Corn grits are obtained through the processing of corn (Zea mays L.), a raw material mainly intended for extrusion and production of derivatives, such as snacks and various types of flour. Due to its rich nutritional composition, corn when improperly stored becomes vulnerable to the development of fungi, mites and insects, compromising its quality and safety. Ozone can reduce corn contamination by microorganisms and also degrade mycotoxins. However, ozonation is not always a beneficial process, as it can cause negative effects associated with its high oxidation potential. This research aimed to ozonize corn grits, at different concentrations, in order to analyze possible changes in sensory characteristics (color and general appearance) and in certain physicochemical quality parameters. The results showed that the ozonation of corn grits in high concentrations (60 mg/L for 480 min) causes changes in the color and aroma of the product, being possible to verify the difference (p< 0.05) of the control both by the instrumental method and through sensory analysis. In this condition, the pH and titratable acidity values are also altered, indicating possible lipid oxidation of the product. Thus, under the conditions evaluated in this research, ozonation of corn grits in a concentration of up to 40 mg of O3/L for 300 min is recommended (using 3 kg of sample). Such conditions can be applied in the ozonation of corn grits with different objectives, mainly in relation to quality control during storage.